Topics in Paraplegia - Dionyssiotis, Yannis (IntechOpen, 2014)
Spinal cord injury related paraplegia changes a person's life in a sudden way. The most important issue for physicians, therapists and caregivers is to manage the complications that arise, and help paraplegic subjects return to a productive integrated life within society. The book Topics in Paraplegia provides modern knowledge in this direction. Addressing hot topics related to paraplegia, ranging from surgical management to research therapies with mesenchymal stem cells, this book could be a valued reference for physiatrists, neurosurgeons, orthopaedic surgeons, neurologists and physical therapists. The book is organized into four sections. The first covers the epidemiology and psychological conditions associated with paraplegia, the second discusses surgical management and common rehabilitation interventions; the third medical complications and special musculoskeletal issues, while the last outlines current research in animals and humans.